Effective Oracle Database 10g security by design - Knox, David C. (McGraw-Hill/Osborne : Oracle Press, 2004)
Oracle security expert David Knox explains how to design and develop an integrated, secure Oracle environment. “In my experience in the security world, including 32 years at the Central Intelligence Agency, I’ve not found anyone with more experience in the theory and practice of protecting your data than David Knox.” --Dave Carey, former Executive Director of the CIA